Synthesis under Normal Conditions and Morphology and Composition of AlF3 Nanowires - Albert Dautov; Kotstantin Kotlyar; Denis Butusov; Ivan Novikov; Aliya Khafizova; Artur Karimov (Nanomaterials, 2023)
AlF3 has interesting electrophysical properties, due to which the material is promising for applications in supercapacitors, UV coatings with low refractive index, excimer laser mirrors, and photolithography. The formation of AlF3-based nano- and micro-wires can bring new functionalities to AlF3 material. AlF3 nanowires are used, for example, in functionally modified microprobes for a scanning probe microscope. In this work, we investigate the AlF3 samples obtained by the reaction of initial aluminum with an aqueous hydrofluoric acid solution of different concentrations. The peculiarity of our work is that the presented method for the synthesis of AlF3 and one-dimensional structures based on AlF3 is simple to perform and does not require any additional precursors or costs related to the additional source materials. All the samples were obtained under normal conditions. The morphology of the nanowire samples is studied using scanning electron microscopy. We performed an intermediate atomic force microscope analysis of dissolved Al samples to analyze the reactions occurring on the metal surface. The surface of the obtained samples was analyzed using a scanning electron microscope. During the analysis, it was found that under the given conditions, whiskers were synthesized. The scale of one-dimensional structures varies depending on the given parameters in the system. Quantitative energy-dispersive x-ray spectroscopy spectra are obtained and analyzed with respect to the feedstock and each other.